Driving Across Stepping Stones - Salmon, Gilly (Proceedings of the International Conference on Networked Learning, 2000)
Interaction between work (thought of as doing) and learning (mastering new knowledge and skills) and between paid work and leisure is predicated to become much more fluid in the future (Steele 1996). With the advent of online learning, this notion becomes real and the role of training to work in new ways and in new online environments becomes of critical importance. There is broadening acceptance and understanding of learning as a socially mediated and constructed process (Billett 1996) and of knowledge as no longer "fixed"(Hendry 1996). Therefore supporting training and education through work-based networks, especially exploiting the interactive benefits of online working, needs to take account of a much wider variety of factors than learning to use appropriate software.